The environmental model of mindfulness - Meaden, James (Frontiers in Social Psychology, 2024)
This paper introduces the environmental model of mindfulness, a novel perspective that conceptualizes mindfulness as an adaptive set of cognitive styles influenced by specific socioecological contexts. Extending upon existing conceptualizations of mindfulness as a cultivated trait or practice, the environmental model describes how mindfulness can also result from cognitive adaptations to immediate-return environments. Through an interdisciplinary synthesis of cognitive psychology, anthropology, and environmental studies, four key factors are identified that foster mindful cognitive styles in immediate-return environments: immediate feedback, observational learning, nature exposure, and interconnected self-construal. By examining Indigenous communities living in immediate-return environments, this paper demonstrates how modern, delayed-return environments may inadvertently suppress innate mindful awareness, suggesting that mindfulness practices might be attempts to recalibrate towards more natural cognitive styles. The environmental model bridges Western medical and Eastern ethical perspectives on mindfulness, offering a unifying framework that acknowledges cognitive, environmental, and cultural influences. This approach not only enriches our understanding of human cognitive functioning but also broadens cultural perspectives on mindfulness, highlighting its manifestations across diverse sociocultural contexts. The model has profound implications for mindfulness research and interventions, providing a foundation for more ecologically valid and culturally sensitive approaches to fostering well-being. It invites a fundamental reconsideration of the relationship between human cognition and the environment, potentially revolutionizing our approach to mental health and cognitive enhancement in an increasingly complex world. This paper stands as a call to action for researchers, clinicians, and policymakers to rethink fundamental assumptions about human cognition and design environments that support our innate capacity for mindful awareness.